Babies in therapy, psychoanalytic interventions for infants and their parents - Anzieu-Premmereur, Christine (Frontiers in Psychiatry, 2022)
Babies in therapy: The study “Psychoanalytic interventions for infants and their parents” conducted on infants through the lens of psychoanalysis and clinical work with both parents and infants all contribute to our knowledge of the nature of early relationship disorders. Psychoanalytic theory's concepts of the depressive position, early defense mechanisms, transference, and psychosomatic reactions to depressive emotions are shown to be crucial in clinical cases, giving therapists new tools for intervention and increasing efficiency. Psychoanalysts have researched the long-lasting effects of early disappointments and the sense of being helplessly abandoned; they emphasize that a disruption in the relationship with the caregiver can produce a psychic economy oriented on the avoidance of anxiety, leaving less energy for development. New parents and their sick infants can benefit from early therapies with therapeutic potential and the possibility of preventing future narcissistic pain issues if they are based on psychoanalytic thinking and knowledge of early symptoms.